Urban and regional data management : UDMS annual 2009 : proceedings of the Urban Data Management Society Symposium 2009, Ljubljana, Slovenia, 24-26 June 2009 /: UDMS annual 2009 : proceedings of the Urban Data Management Society Symposium 2009, Ljubljana, Slovenia, 24-26 June 2009. (©2009) - Unknown
No abstract available